Meningkatkan Etika Komunikasi Generasi Z dalam Berkomunikasi melalui WhatsApp - Muhammad Maududi, Mukhlish; Romadlan, Said; Rahman, Nurlina (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service program is to improve teenagers' understanding of ethics in communicating through WhatsApp. The implementation method of this program includes three main stages, namely lectures, discussions, questions and answers, and practice. Through lectures, participants were given a strong understanding of the importance of ethics in communicating online and knowledge of the Electronic Information and Transaction Law relating to communication ethics. Discussion and Q&A sessions allowed participants to share their experiences and views, so that they could learn from each other. Hands-on practice allowed participants to implement their knowledge in real situations, so they could develop better communication skills. This program only involved 19 teenagers. Therefore, it is necessary to conduct follow-up activities involving more participants from various backgrounds to generalize the results of this activity. This program has significant practical implications, which can help create a more civilized online environment and avoid negative behaviors such as insinuating and blaspheming fellow social media users as well as increasing public awareness about the importance of ethics in communicating through social media.